Dissecting X-Ray Raman Resonances Using Four-Wave Mixing - Govind Niranjan; Healion Daniel; Zhang Yu; Biggs Jason D.; Shaul Mukamel (EPJ Web of Conferences, 2013)
The stimulated x-ray Raman signal has been calculated for the amino acid cysteine using broadband (FWHM ≃14.2eV, 128 as) pulses tuned to the nitrogen K-edge. Peaks correspond to those valence excited states and reveal electronic Frank-Condon overlaps between canonical valence orbitals and relaxed orbitals in the presence of the core hole. The coupling between excited states with valence- and core-holes is further explored using a coherent, wave-vector matched photon echo technique, where it is possible to eliminate stimulated emission and excited-state absorption by taking the waiting time to be longer the lifetime of the core hole (∼ 7:1 fs for nitrogen).